Structural rigidity of the I–II loop couples Ca V β anchoring to Ca V 2.2 gating modes - Jin-Nyeong Woo; Jung-Eun Kim; Byung-Chang Suh (Proceedings of the National Academy of Sciences, 2026)
The auxiliary β subunits of voltage-gated Ca 2+ (Ca V ) channels are fundamental regulators of channel gating and neuronal excitability. While the subcellular localization of β subunits is known to influence current density and inactivation, the precise kinetic mechanism by which they differentially modulate channel opening and closing remains elusive. Here, we report a kinetic paradox in Ca V 2.2 channels: membrane-anchored β subunits decelerate current decay during depolarization yet accelerate tail deactivation upon repolarization, whereas cytosolic β subunits promote rapid decay but prolong deactivation. Using quantitative kinetic analysis and Markov state modeling, we demonstrate that macroscopic current decay is not solely a monolithic irreversible inactivation process but a composite of irreversible inactivation and a reversible transition to a nonconducting state. We reveal that membrane-anchored β subunits suppress the transition to this reversible nonconducting state, thereby maintaining the open state, while facilitating a rapid return from the nonconducting state to prevent kinetic trapping. Furthermore, by manipulating the linker length of β subunits and engineering the I–II loop hinge region (R370), we identify that the physical proximity of the β subunit to the plasma membrane, coupled with the structural rigidity of the I–II loop, acts as a mechanical determinant that governs this gating pathway selection. Our findings provide a unified gating model in which the β subunit fine-tunes the dynamic equilibrium between conducting and nonconducting states via mechanical constraint on the channel complex, offering a comprehensive resolution to the distinct regulation of Ca V 2.2 kinetics.